Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China - Starkevich, Pavel; Men, Qiu-Lei; Saldaitis, Aidas (Zootaxa, 2019)
Four new crane fly species of subgenus Tipula (Vestiplex) Bezzi, 1924, T. (V.) borthi sp. nov. (Sichuan, Qinghai and Gansu provinces, erectiloba species group), T. (V.) maoxianensis sp. nov. (Sichuan province, virgatula species group), T. (V.) xinduqiaoensis sp. nov. and T. (V.) auriculatalobata sp. nov. (Sichuan and Yunnan provinces, divisotergata species group) are described and illustrated. The newly described species can be separated using the identification keys provided for local species of the erectiloba, virgatula and divisotergata groups.